Uruguay : 2009 Article IV Consultation; Staff Report; Staff Statement and Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Uruguay. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
This 2009 Article IV Consultation highlights that the Uruguayan economy has held up considerably well in the face of the global recession. The impact of the crisis appears to have been relatively short lived. Private consumption and investment decelerated while the unemployment rate rose only little and temporarily. The policy response to the crisis has sought to balance different risks. Executive Directors have welcomed the achievement of single-digit inflation over the last several years, while noting that inflation remains relatively high.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet